EFFECTIVENESS OF SIMULATION-BASED LEARNING IN NURSING EDUCATION: AN OBSERVATIONAL ANALYSIS BASED ON STUDENT FEEDBACK (Ustozlar uchun, 2025)
Simulation-based learning has become an essential component of modern nursing education, enabling students to develop clinical skills in a safe, controlled, and experiential environment. This observational study analyzes feedback collected from nursing students regarding their experience with simulation technologies during their educational process. The aim is to assess students’ perceptions of the usefulness, effectiveness, and adequacy of simulation-based training within their curriculum. Data were derived from a structured questionnaire administered to students of a nursing education program. The results show a high level of acceptance and perceived effectiveness of simulation technologies, though students report certain gaps in the frequency of sessions, realism of scenarios, and instructor engagement. The findings suggest that simulation-based methods improve confidence, practical readiness, and decision-making abilities among nursing students. Recommendations are provided to strengthen simulation integration into professional nursing education.